Continuing the acoustic investigation of nasals in the contemporary Baltic languages: a comparative study - Urbanavičienė, Jolita; Taperte, Jana (Baltistica, 2022)
In the paper, the nasals of the contemporary Baltic languages have been analyzed: labial (Lith. /m/, /mj/ and Lat. /m/), dental (Lith. /n/, /nj/ and Lat. /n/), palatal (Lat. /ɲ/), as well as [ŋ], the velar allophone of /n/ which occurs before [–k/–g] in both languages. Four acoustic properties of Lithuanian and Latvian nasals have been investigated: 1) the first nasal formant (N1); 2) the bandwidth of the first nasal formant (B1); 3) the frequency range of the antiformant (Z1); 4) F2 loci. The study material included three Lithuanian and three Latvian native speakers (men aged 20–40). Lithuanian and Latvian sonorants were analyzed in a prevocalic position in CVC sequences taking into account two criteria: 1) the place of articulation; 2) palatalization (non-palatalized vs. palatalized vs. palatal nasal). According to the results, the investigated acoustic properties of nasals in Baltic have different relevance in distinguishing between different places of articulation: 1) N1 is relevant when distinguishing between the velar allophones [ŋ, ŋʲ] and the rest of the nasals in both languages; 2) there is a statistically significant difference in B1 values of Lithuanian dental/palatalized and non-palatalized labial/velar nasals, as well as Latvian labial/dental and palatal/velar nasals; 3) in terms of Z1 frequencies, it is possible to differentiate Lithuanian [m, mʲ, n, nʲ] from [ŋ, ŋʲ]; in Latvian, it is possible to distinguish between all places of articulation by Z1 values: [m] < [n] < [ɲ] < [ŋ]; 4) F2 loci can be considered as one of the most important cues for differentiating places of articulation of Lithuanian and Latvian nasals, although they do not distinguish between all the nasal places of articulation classes in Baltic. The study has shown that there is no single distinctive acoustic feature that would distinguish between all the nasals, therefore nasal sonorants must be investigated comprehensively. Perceptual experiments would also help to assess the differential significance of acoustic properties.